Blackberry and raspberry are alternative resistance sources to fire blight - Calis, Ozer; Cekic, Cetin; Kara, Serhat; Celik Ertekin, Demet (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2017)
Erwinia amylovora causes fire blight mainly on pear, apple and quince trees. This bacterial pathogen also infects other Rosaceous plants, such as blackberry and raspberry. A race structure was established between an isolate of E. amylovora and berries using 40 wild blackberry and 7 wild raspberry genotypes. In pathogenicity tests, wild blackberry and raspberry genotypes had three phenotypic reactions: enhanced susceptibility, moderate susceptibility and resistance. We noted a higher bacterial growth of over 300 × 109 cfu mL-1 in plants with enhanced susceptibility, with resistant genotypes showing a bacterial growth of around 150 × 109 cfu mL-1. These results are also associated with symptoms observed at 29 days post-inoculation. This resistance is being evaluated to control fire blight.